The Influence of Homologous and Heterologous Sera in Culture Medium on in Vitro Maturation and Fertilization of Sheep Oocytes - Ita Djuwita; Yohan Rusyiyantono; Kusdiantoro Muhamad; Bambang Purwantara; Yuhara Sukra (Media Veteriner, 1998)
The influence of various types of sera i.e. Fetal Calf Serum (FCS), Bovine Post Estrous Serum (SPES) as heterolog sera; and Ewes Fetal Serum (EFS) and Ewes Serum (ES) as homologue sera on in vitro maturation and fertilization of sheep oocytes was investigated using Tissue Culture Medium 199TM (TCM 199. Gibco). Sovine sera were collected from cow at seven days post-estrus, while ewes sera were collected during estrous (ES-HO) and six days post estrous (ES-H6). The result shows that the maturation rate of oocytes cultured in medium supplemented with EFS, ES-HO and ES-H6 at concentrations of 32.9%, 68.7%, and 67.6% respectively is better than those supplemented with FCS and SPES at concentrations of 22.2% and 28.9%, respectively. In vitro fertilization rate were significantly higher in medium supplemented with ES-HO and ES-H6 at concentration of 65.4% and 65.8% (P < 0.05) than that supplemented with SPES at concentration of 31.7%. In conclusion, ewes sera could be used in culture medium for promoting both in vitro maturation and fertilization rate of sheep oocytes.